Rethinking sustainability in facilities and workplace management - Melissen, Frans; Danivska, Vitalija; Smit, Bert; Mzembe, Andrew Ngawenja (London Routledge, Taylor & Francis Group, 2023)
This book discusses sustainability within the facility management industry, based on the realisation that most facility management businesses and departments actually find it hard to truly integrate sustainability into their strategies, tactics and day-to-day operations in a coherent way. --
Sustainability, facilities and workplace management -- Technology and behaviour -- People and sustainability -- Identity and sustainability -- Local stakeholders and sustainability -- Sustainable business model logic and competencies.
Includes bibliographical references and index.
Keywords: Facility management -- Environmental aspects; Sustainable development; Social responsibility of business; Work environment